2015
DOI: 10.4028/www.scientific.net/amm.805.180
|View full text |Cite
|
Sign up to set email alerts
|

Automated Pattern Recognition in Load Profiles of Milling Operations

Abstract: Due to the introduction of an energy management system, a lot of existing manufacturing plants were equipped with energy measurement systems. With sufficient sample rates those retrofitted energy measuring systems could provide additional information beside active power and energy consumption. Each production plant is characterized by a process and product specific power consumption with an associated power signal. In this paper a method to determine the information content in power signals of milling operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Due to the high flexibility and fast adaptation possibilities of the system, sensors and sampling rates can easily be adapted for investigation on process, machine or even component level. Even Götze, Hamacher, Reger, et al confirmed in [18,20,21] that the precise adjustment of the measuring system is critical for the analysis.…”
mentioning
confidence: 99%
“…Due to the high flexibility and fast adaptation possibilities of the system, sensors and sampling rates can easily be adapted for investigation on process, machine or even component level. Even Götze, Hamacher, Reger, et al confirmed in [18,20,21] that the precise adjustment of the measuring system is critical for the analysis.…”
mentioning
confidence: 99%